Results of dose-dense neoadjuvant chemotherapy in the treatment of stages IB2-IIB cervical cancer - A. S. Mamontova; O. A. Smirnova; A. O. Nyuganen; A. V. Abramova; S. S. Bagnenko; A. F. Urmancheeva; E. A. Ulrich; A. V. Mishchenko; I. V. Berlev (ABV-press, 2023)
Background. Applied standard methods of cervical cancer (CC) treatment have several disadvantages in terms of local and systemic toxicity and the risks of local recurrence. Our study proposed the use of neoadjuvant chemotherapy (NACT) in a dose-dense mode, followed by radical hysterectomy, in order to improve the results of treatment of locally advanced CC (IB2-IIB stages) (FIGO)/T1b2-2bN0M0 (TNM).Aim. Improvement of immediate and long-term results in treatment of locally advanced CC IB2-IIB stages (FIGO), determining the immediate effectiveness of dose-dense NACT, based on magnetic resonance imaging (MRI) data, and the identification of prognostic factors for tumor response to chemotherapy.Materials and methods. Between April 2016 to November 2019 120 women with IB2-IIB stages (FIGO) were included in this study. Of these, 58 patients underwent 3 cycles of intensified NACT according to the AP scheme (cisplatin 75 mg/m2, doxorubicin 35 mg/m2) and 62 patients underwent NACT according to the TR scheme (cisplatin 60 mg/m2, paclitaxel 60 mg/m2). The assessment of the effect of intensified NACT was performed according to the RECIST 1.1 criteria according to MRI data. Also 2 retrospective groups of patients were recruited: group I - surgical treatment without preoperative chemotherapy (25 patients with IB2-IB3 stages (FIGO) from November 2009 to August 2019), group II - concurrent chemoradiotherapy (44 patients with stage IIB cervical cancer (FIGO) from January 2013 to June 2018).Results. Complete clinical response was detected in 12 (10.0 %) patients, partial response - in 69 (57.5 %) patients, stable disease - in 35 (29.2 %) patients, progression was observed in 4 cases (3.3 %). After NACT in a dose dense mode, due to an objective clinical response (complete response, partial response and stable disease for stage IIA according to RECIST 1.1 criteria), 99 (82.5 %) patients underwent surgical treatment. For 21 (17.5 %) patients due to the absence achievement of objective clinical response (stable disease for stage IIB according to RECIST 1.1 criteria or progression), performed concurrent chemoradiotherapy. During the observation period, 113 (94.2 %) patients remained alive. Mortality for the first year was 1.7 % (2 cases). There was a coincidence of the results of a complete response according to MRI in 11 (91.7 %) cases out of 12 cases with the pathology data. According to multivariate analysis, it was revealed that parametrial invasion, according to the histological examination of the surgical material, is an independent prognostic factor for recurrence. According to comparative evaluation of disease-free survival curves between groups of IB2-IIB stages (FIGO) patients who received and did not receive dose-dense chemotherapy, it was found that disease- free survival in the group with NACT was higher compared to the group without NACT (p = 0.03, the log-rank criterion).Conclusions. The use of dose-dense NACT is an effective treatment mode for patients with IB2-IIB CC (FIGO), which in most cases allows achieving a tumor response with subsequent improvement in immediate and long-term results and can be considered as an alternative to standard treatment for locally advanced CC.